Perjanjian Jual Beli Pohon Musiman Di Dalam Masyarakat Desa Sanahu Seram Bagian Barat - Julian Marsel Kaisiry; Barzah Latupono; Sarah Selfina Kuahaty (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The sale and purchase agreement has undergone many developments, especially regarding the procedures or forms used.Purposes of the Research: This writing aims to analyze the customary law review of the seasonal tree sale and purchase agreement in the Sanahu State community, to find out the form of sanctions for buyers who do not carry out the custom of buying and selling seasonal trees in accordance with customary law in the Sanahu State community, as one of the requirements in fulfilling study completion at the Faculty of Law, University of Pattimura.Methods of the Research: Normative juridical research method, which is to obtain data from the library in the form of documents, books, magazines and other literature related to writing. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through qualitative analysis, namely the data obtained and then arranged systematically for further qualitative analysis based on scientific disciplines. Civil law to achieve clarity of issues to be discussed.Results of the Research:  The results of the study show that the tree sale and purchase agreement in the Sanahu community is valid, because it complies with the Civil Code contained in Article 1320, namely regarding the terms of the agreement. The agreement that has been agreed upon by the parties regarding prices and goods, is capable of making an agreement.